Outer Membrane Machinery and Alginate Synthesis Regulators Control Membrane Vesicle Production in Pseudomonas aeruginosa - Tashiro, Yosuke (American Society for Microbiology (ASM), 2009)
The opportunistic human bacterial pathogen Pseudomonas aeruginosa produces membrane vesicles (MVs) in its surrounding environment. Several features of the P. aeruginosa MV production mechanism are still unknown. We previously observed that depletion of Opr86, which has a role in outer membrane protein (OMP) assembly, resulted in hypervesiculation. In this study, we showed that the outer membrane machinery and alginate synthesis regulatory machinery are closely related to MV production in P. aeruginosa. Depletion of Opr86 resulted in increased expression of the periplasmic serine protease MucD, suggesting that the accumulation of misfolded OMPs in the periplasm is related to MV production. Indeed, the mucD mutant showed a mucoid phenotype and the mucD mutation caused increased MV production. Strains with the gene encoding alginate synthetic regulator AlgU, MucA, or MucB deleted also caused altered MV production. Overexpression of either MucD or AlgW serine proteases resulted in decreased MV production, suggesting that proteases localized in the periplasm repress MV production in P. aeruginosa. Deletion of mucD resulted in increased MV proteins, even in strains with mutations in the Pseudomonas quinolone signal (PQS), which serves as a positive regulator of MV production. This study suggests that misfolded OMPs may be important for MV production, in addition to PQS, and that these regulators act in independent pathways.